Hbr's 10 must reads for sales and marketing collection 5 books (HBR's 10 must reads (Series), 2020)
Stop pushing products. Start empowering your salespeople cultivating relationships with the right customers. In today's economy, companies are fighting tooth and nail for their customers' attention. Hyper-informed buyers with more options are making purchasing decisions faster than ever. How can you optimize your marketing operations and sales teams and so your offerings can get through and rise to the top' HBR's 10 Must Reads for Sales and Marketing Collection offers the ideas and strategies to help you get there. Included in this set are HBR's 10 Must Reads on Sales, HBR's 10 Must Reads on Strategic Marketing, HBR's 10 Must Reads on Communication, HBR's 10 Must Reads on Negotiation, and HBR's 10 Must Reads on Public Speaking and Presenting. This compilation offers insights from world-class experts on the topics including enhancing the joint performance of sales and marketing; motivating your sales force; getting a clear view of your brand's strengths and weaknesses; setting the stage for a successful negotiation; and communicating with clarity and impact. It includes fifty articles selected by HBR's editors from renowned thought leaders such as Andris Zoltners, Theodore Levitt, and Deborah Tannen, and features the indispensable article "How to Give a Killer Presentation" by Chris Anderson. It's time to establish, sustain, and extend your next groundbreaking sales and marketing initiative. HBR's 10 Must Reads for Sales and Marketing Collection will lead you there. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected